Derivative of The Sine Function

In my last note I proved that limθ0θsinθ=1 \quad\displaystyle \lim_{\theta\to 0}\frac { \theta}{sin\theta} = 1

If you have not read that I would recommend reading that first as this limit is used in proving the derivative of the sine function. Here is the link.

limθ0θsinθ=? \qquad \qquad\qquad\qquad\qquad\qquad \displaystyle \lim_{\theta\to 0}\frac { \theta}{sin\theta} = ?

To prove the derivative of the sine function we will be using the first principles of derivatives.

limΔθ0sin(θ+Δθ)sinθΔθ\qquad\qquad\qquad\qquad\qquad\displaystyle \lim_{\Delta\theta\to 0}\frac{\sin(\theta + \Delta\theta) - \sin\theta}{\Delta\theta}

Use the addition formula for sin(θ+Δθ)\sin(\theta + \Delta\theta).

=limΔθ0sinθ×cosΔθ+sinΔθ×cosθsinθΔθ=\qquad\qquad\qquad\quad\displaystyle\lim_{\Delta\theta\to 0} \frac{\sin\theta \times \cos \Delta\theta + \sin\Delta\theta \times \cos\theta - \sin\theta}{\Delta\theta}

rearrange the equation and factor out sinθ\sin\theta

=limΔθ0sinθ×cosΔθsinθ+sinΔθ×cosθΔθ=\qquad\qquad\qquad\quad\displaystyle\lim_{\Delta\theta\to 0} \frac{\sin\theta \times \cos \Delta\theta - \sin\theta + \sin\Delta\theta \times \cos\theta }{\Delta\theta}

=limΔθ0sinθ(cosΔθ1)+sinΔθ×cosθΔθ=\qquad\qquad\qquad\quad\displaystyle\lim_{\Delta\theta\to 0} \frac{\sin\theta( \cos \Delta\theta - 1) + \sin\Delta\theta \times \cos\theta }{\Delta\theta}

break apart the fraction

=limΔθ0sinθ(cosΔθ1)Δθ+sinΔθ×cosθΔθ=\qquad\qquad\qquad\quad\displaystyle \lim_{\Delta\theta\to 0}\frac{\sin\theta( \cos \Delta\theta - 1)}{\Delta\theta} + \frac{\sin\Delta\theta \times \cos\theta }{\Delta\theta}

=limΔθ0sinθ×(cosΔθ1)Δθ+sinΔθΔθ×cosθ=\qquad\qquad\qquad\quad\displaystyle \lim_{\Delta\theta\to 0}\sin\theta \times \frac{( \cos \Delta\theta - 1)}{\Delta\theta} + \frac{sin\Delta\theta}{\Delta\theta} \times cos\theta

We wIll now evaluate the two limits seperately

limΔθ0sinΔθΔθ×cosθ\qquad\qquad\qquad\quad\displaystyle \lim_{\Delta\theta\to 0} \frac{sin\Delta\theta}{\Delta\theta} \times cos\theta

In my last note I proved that limΔθ0sinΔθΔθ=1\displaystyle\lim_{\Delta\theta\to 0}\frac{sin\Delta\theta}{\Delta\theta}=1

=limΔθ01×cosθ=\qquad\qquad\qquad\quad\displaystyle \lim_{\Delta\theta\to 0} 1 \times cos\theta

=limΔθ0cosθ=\qquad\qquad\qquad\quad\displaystyle \lim_{\Delta\theta\to 0} cos\theta

That solves that limit now the other limit.

limΔθ0sinθ×(cosΔθ1)Δθ\qquad\qquad\qquad\quad\displaystyle \lim_{\Delta\theta\to 0}\sin\theta \times \frac{( \cos \Delta\theta - 1)}{\Delta\theta}

divide out the sinθ\sin\theta

=sinθlimΔθ0(cosΔθ1)Δθ=\qquad\qquad\qquad\quad\displaystyle \sin\theta \lim_{\Delta\theta\to 0} \frac{( \cos \Delta\theta - 1)}{\Delta\theta}

multiply by the conjugate

=sinθlimΔθ0(cosΔθ1)Δθ×cosΔθ+1cosΔθ+1=\qquad\qquad\qquad\quad\displaystyle \sin\theta \lim_{\Delta\theta\to 0} \frac{( \cos \Delta\theta - 1)}{\Delta\theta} \times \frac{\cos\Delta\theta+1}{\cos\Delta\theta+1}

=sinθlimΔθ0(cos2Δθ1)Δθ(cosΔθ+1)=\qquad\qquad\qquad\quad\displaystyle \sin\theta \lim_{\Delta\theta\to 0} \frac{( \cos^{2} \Delta\theta - 1)}{\Delta\theta(\cos\Delta\theta+1)}

Rewrite the the equation using the Pythagorean identity. cos2θ+sin2θ=1 \cos^{2}\theta + \sin^{2}\theta=1

=sinθlimΔθ0sin2ΔθΔθ(cosΔθ+1)=\qquad\qquad\qquad\quad\displaystyle \sin\theta \lim_{\Delta\theta\to 0} \frac{-\sin^{2} \Delta\theta }{\Delta\theta(\cos\Delta\theta+1)}

break apart the fraction

=sinθlimΔθ0(sinΔθ)×sinΔθΔθ×1cosΔθ+1=\qquad\qquad\qquad\quad\displaystyle \sin\theta \lim_{\Delta\theta\to 0} (-sin\Delta\theta) \times \frac{\sin\Delta\theta}{\Delta\theta} \times \frac{1}{\cos\Delta\theta + 1}

evaluate the limits

=sinθ×(sin0)×1×1cos0+1=\qquad\qquad\qquad\quad\displaystyle \sin\theta \times (-sin0) \times 1 \times \frac{1}{\cos0 + 1}

=sinθ×0×1×12=\qquad\qquad\qquad\quad\displaystyle \sin\theta \times 0 \times 1 \times \frac{1}{2}

=0=\qquad\qquad\qquad\quad\displaystyle 0

Now add both limts.

ddθ=limΔθ0sinθ×(cosΔθ1)Δθ+limΔθ0sinΔθΔθ×cosθ \displaystyle \frac{d}{d\theta}=\qquad\qquad\qquad\quad \lim_{\Delta\theta\to 0}\sin\theta \times \frac{( \cos \Delta\theta - 1)}{\Delta\theta} + \lim_{\Delta\theta\to 0}\frac{sin\Delta\theta}{\Delta\theta} \times cos\theta

ddθ=0+cosθ \displaystyle \frac{d}{d\theta}=\qquad\qquad\qquad\quad0 + \cos\theta

ddθ=cosθ \displaystyle \frac{d}{d\theta}=\qquad\qquad\qquad\quad \cos\theta

Note by Brody Acquilano
6 years, 2 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link]( link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}


There are no comments in this discussion.


Problem Loading...

Note Loading...

Set Loading...